2019
DOI: 10.1038/s41598-019-40016-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome targeted gene quantification provides new insights on pulmonary sarcomatoid carcinomas

Abstract: Pulmonary sarcomatoid carcinomas (PSC) are a rare group of lung cancer with a median overall survival of 9–12 months. PSC are divided into five histotypes, challenging to diagnose and treat. The identification of PSC biomarkers is warranted, but PSC molecular profile remains to be defined. Herein, a targeted whole transcriptome analysis was performed on 14 PSC samples, evaluated also for the presence of the main oncogene mutations and rearrangements. PSC expression data were compared with transcriptome data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…In recent studies, MET exon 14 skipping mutations were found to be enriched in PSC, and the incidence rate was as high as 31.8% (20), which could be a potential target for therapy using MET inhibitors, such as volitinib, capmatinib, and tepotinib (21)(22)(23). In addition, patients with PSC had an increased tendency for the high expression of tumor mutation burden (>20 mutations per Mb) compared with those with oNSCLC (20% vs 14%, P = 0.056) (22).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, MET exon 14 skipping mutations were found to be enriched in PSC, and the incidence rate was as high as 31.8% (20), which could be a potential target for therapy using MET inhibitors, such as volitinib, capmatinib, and tepotinib (21)(22)(23). In addition, patients with PSC had an increased tendency for the high expression of tumor mutation burden (>20 mutations per Mb) compared with those with oNSCLC (20% vs 14%, P = 0.056) (22).…”
Section: Discussionmentioning
confidence: 99%
“…The read counts per gene were defined using feature count [ 23 ] as the reference transcriptome. Differential expression analysis was performed using edgeR R package [ 24 ], and the tumor samples were compared to their matched normal samples to identify DEGs. The selected genes are significantly differentially expressed between tumor and normal samples and their FDR < 0.05 and absolute log2 fold change (logFC) > 1.…”
Section: Methodsmentioning
confidence: 99%
“…In a gene enrichment analysis, the Fanconi anemia (FA) pathway was indicated in addition to the above mentioned biological processes. Interestingly, this pathway was reported in connection with EGFR resistance by other groups [41,42,43,44]. Pfaffle et al explicitly described an FA phenotype in EGFR resistant cells and a possible susceptibility of these cells towards PARP inhibition [43].…”
Section: Discussionmentioning
confidence: 98%